Crisis of the Rule of Law in the EU through the Case Law of the ECJ: The Case of Poland - Oikonomou, Kassiani (HAPSc Policy Briefs Series, 2020)
This article describes the rule of law crisis in Poland through the case law of the ECJ. In particular, the country in 2018 adopted the law on the Supreme Court, bringing about two changes; the reduction of the retirement age for judges and secondly, it gave the President of the Republic of Poland the discretion to extend the active judicial service of judges of the Supreme Court. This article concerns the case C-619/18 Commission v Republic of Poland, in which the Commission in 2018 pursuant to Article 258 TFEU appealed to the Court of Justice of the European Union, seeking to prove that this law violates the obligations of Article 19 (1) paragraph 47 TEU in conjunction with Article 47 of the Charter, with the Commission claiming that these provisions infringe both the principle of permanence and the principle of the independence of judges.